The effectiveness of the implementations on the safety and health practices at construction site in Kuantan - Iffah Billah, Nor Hashim (2014)
In the era of technology advancement and sophisticated, Malaysia is among of the developing country with the increasing of residents. There are many of new project being launched include with the construction. The types of construction consist of residential, heavy projects, industrial and building. The observation of fifty five (55) construction sites at Kuantan in 2013 was investigated for the state of safety and health. The questionnaires have been distributed to the 98 respondents and the data analyzed throughout the relative average index. At each site, the workers, construction projects and the physical environment of the site were evaluated and inspected against safety and health taken from the literature. The results tell that the accident reported cases in construction site in Kuantan, is serious even though the number is low compared to other industries and it should be taken seriously. Interviews with workers indicated that injuries and accidents are common on sites. While the frequencies of accidence happen is one in a month during the construction project time. It may be different from the data collected from SOSCO it is because the employer did not make a report.